Computational modeling of homogeneous catalysis - Maseras, Feliu; Lledós, Agustí (Catalysis by metal complexes, 2002)
Recent results on a wide array of catalytic processes are collected in this volume. The book illustrates the importance of computational modelling in homogeneous catalysis by providing up-to-date reviews of its application to a variety of reactions of industrial interest.